(untitled) (Journal of Education Culture and Society, 2020)
The article describes the role of interdisciplinarity in the process of making science. Two patterns of research and development of discipline are presented: the closed pattern which concentrates on specialization and the open pattern which fosters interdisciplinary science. The key to success is always openness for new scientific experiences and communities. The conclusion of the article is a proposal for finding new scientific communities, which could be interested in new ideas, research and thoughts where interdisciplinary analyses are not acceptable to the local scientific community.